Evaluation of Absorbable and Nonabsorbable Sutures for Repair of Achilles Tendon Rupture With a Suture-Guiding Device. (June 2015) - Kocaoglu, Baris; Ulku, Tekin Kerem; Gereli, Arel; Karahan, Mustafa; Turkmen, Metin
Background: The purpose of this study was to compare the functional and clinical results of Achilles tendon repairs with an Achilles tendon suture-guiding device using nonabsorbable versus absorbable sutures. We hypothesized that the absorbable suture would have clinical results comparable to those of the nonabsorbable suture for Achilles tendon repair with an Achilles tendon suture-guiding system. Methods: From January 2010 to September 2013, 48 consecutive patients who had sustained a spontaneous rupture of the Achilles tendon underwent operative repair with an Achilles tendon suture-guiding device using 2 different suture types. All ruptures were acute. The patients were divided equally into 2 groups according to suture type. In the nonabsorbable suture group, No. 2 braided nonabsorbable polyethylene terephthalate sutures were used, and in the absorbable suture group, braided absorbable polyglactin sutures were used. The average age of the patients was 38 years (range, 28-50 years). Functional outcome scores and complications were evaluated. Results: All patients had an intact Achilles repair after surgery. The American Orthopaedic Foot & Ankle Society (AOFAS) hindfoot clinical outcome scores were 98 (range, 90-100) in the nonabsorbable suture group and 96.8 (range, 87-100) in the absorbable suture group. All patients returned to their previous work. The absorbable suture group had fewer postoperative complications (0%) than the nonabsorbable suture group (12.5%) ( P < .05). Conclusion: Use of an absorbable suture in the treatment of Achilles tendon repair by an Achilles tendon suture-guiding system was associated with a lower incidence of suture reaction; however, functionally the results were not notably different from those using a traditional nonabsorbable suture. We conclude that repair with absorbable sutures is appropriate for Achilles tendon ruptures. Level of Evidence: Level II, prospective comparative study.